GAME EDUKASI AKUNTANSI SEBAGAI SARANA PENINGKATAN MINAT BELAJAR SISWA (STUDI KASUS : SMK NEGERI 8 BANDAR LAMPUNG) - Yohana Tri Utami (Jurnal Tekno Kompak, 2019)
The learning process will be a matter of accounting requirements. The subject of accounting adjusting journal entries is a subject that is very difficult to understand for student class X because in the learning there are abstract calculation elements and do not have a formula as well as lessons that use other calculations and students feel bored with conventional learning. The purpose of this study was to design and build educational game applications as a means of increasing student learning interest.Data collection techniques in this research is to use interviews, questionnaires, and review of the literature. Sources of data / subjects are students of SMK N 8 Bandar Lampung. Methods of testing conducted on aspects ie Usability, Functionality, Efficiency, and Portability. Accounting application development educational game built using Construct 2 software that will run on android platform.The results of testing the quality of game applications obtained values from usability aspects obtained 96%, 99% aspect functionality, efficiency aspects showed no memory shortages and CPU usage by applications by 47%, and the portability aspect of the application can only be installed and run on the device with Android version of Jelly Bean and above.